Analisis Resepsi terhadap Feminisme dalam Film Birds of Prey - Eryca Septiya Ningrum; Ineza Vedya Prishanti; Anjani Syafitri Ditasyah; Ifda Faidah Amura (Jurnal Syntax Transformation, 2021)
Feminism is a movement to fight for gender equality between men and women. Many efforts have been made to support feminism, one of which is by using films. Film is a mass media that is persuasive enough to sedate the audience. Apart from being entertaining, films are also realistic media in depicting social, political economy and other problems. This study aims to determine the audience position from the three positions of readers stated by Stuart Hall through the film "Birds Of Prey" which shows feminism. This research uses qualitative research methods with reception analysis methods. The conclusion of this study, there are two informants who occupy a dominant hegemony position, 1 informant on the opposition position, and 1 informant in the negotiation position.